AN ANALYSIS ON THE FUNCTION AND ACCURACY OF COORDINATE CONJUNCTION AND IN TRANSLATING A NOVEL CONFESSION OF SHOPAHOLIC - Hadita Hadita (LPPM Universitas Bina Sarana Informatika, 2014)
This research is about the function and the accuracy of coordinate conjunction and in translating a novel Confession of Shopaholic. The purpose of this research are to describe whether the coordinate conjunction and in TLhas same function or not in SL andto describe the accuracy in translating coordinate conjunction and that is not translated into dan. The research methodology used isdescriptive method focusing on describing the function and the accuracy of translation in translating coordinate conjunction andand the theories used: the theory of coordinate conjunction in English and Indonesian, the function of coordinate conjunction andand the theory of accuracy. The finding of this research show when the coordinate conjunction and not translated into dan, the meaning ofcoordinate conjunction and remains the same in TL